HIV and Other Sexually Transmitted Infections among Men Who Have Sex with Men Recruited by RDS in Buenos Aires, Argentina: High HIV and HPV Infection - Pando, María A.; Balán, Iván C.; Marone, Rubén; Dolezal, Curtis; Leu, Cheng-Shiun; Squiquera, Luis; Barreda, Victoria; Rodriguez Fermepín, Marcelo; Gallo Vaulet, Lucia; Rey, Jorge; Picconi, María; Carballo-Diéguez, Alex; et al. (PLOS ONE, 2012)
Background The aim of this study was to estimate the prevalence of HIV and other STIs, among MSM from Buenos Aires (2007–2009). Methods Responding Driven Sampling was used for recruitment of MSM. Participants completed a structured web-based survey and provided biological samples. Results A total of 496 MSM were studied for HIV, HBV, HCV, and T pallidum infections. Chlamydia and HPV diagnoses were only performed in 98 and 109 participants, respectively. Prevalence of HIV was 17.3%, HBV 22.9%, HCV 7.5%, T pallidum 20.5%, HPV 83.5%, and C trachomatis 1.7%. In the year prior to the evaluation, 71% of the participants had had sex with men and/or trans and women (MMW) while 29% had not had sex with women (MM). Comparing MM to MMW, prevalence of HIV (30.7% vs. 11.9%, p<0.001), HBV (36.4% vs. 17.8%, p<0.001), T pallidum (32.1% vs. 15.7%, p<0.001), and HPV (88.3% vs. 70.4%, p = 0.039) were significantly higher among MM, whereas no significant differences were found for HCV and C trachomatis. The MM group had also significantly higher HIV incidence (5.60 vs. 4.28 per 100 persons-year, p = 0.032). HPV genotypes 16, 6, and 11 were the most frequently found; 40.7% of the MSM had more than one genotype and one high risk genotype was detected in 43.6% of participants. Conclusions Both MM and MMW are at high risk of infection for HIV and other STIs. Rates of HIV, HBV, T pallidum and HPV infections are higher in the MM group.